SURVEI TINGKAT KEPUASAN SISWA TERHADAP KETERSEDIAAN SARANA DAN PRASARANA PJOK DI SMA NEGERI 10 GOWA - Mesfer, Nabila; Ismail, Agus; Walinga, Andi Nahdia T (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2025)
This study aimed to determine the level of student satisfaction with the availability of Physical Education facilities and infrastructure at SMA Negeri 10 Gowa. This study was a type of quantitative descriptive research with a survey method. The sample in this study were 90 students of SMA Negeri 10 Gowa. This research instrument used a questionnaire consisting of 49 statement items. The result of the instrument validity test with Pearson’s product moment correlation showed that there was a correlation with a significance level of 0.05 of 0367 (df29) with an alpha reliability coefficient value of 0.952 so that the instrument was reliable. The data analysis technique used was quantitative descriptive statistics with percentages. The result of the study showed that the level of students’ satisfaction with the availability of PJOK facilities and infrastructure at SMA Negeri 10 Gowa was in the category of “very satisfied” at 5.56% (5 students). “satisfied” at 24.44% (22 students), “quite satisfied” at 45.56% (41 students), “dissatisfied” at 14.44% (14 students), and “very satisfied” at 10% (9 students).